Relationship between economic growth and the environment in Ecuador at the provincial level (Average 2010-2015) - García, Diana J. (2017)
This research analyzes the relationship between economic growth and the environment in Ecuador at the provincial level using average information from 2010-2015. For this, the main economic and environmental variables were selected: population density, illiteracy rate, gross added value, economically active population, average total household income, carbon dioxide emissions (CO2) and average annual deforestation. In the methodology used, in the first instance the calculation of the averages of the variables was carried out, later an environmental damage index was developed which was correlated with each of the economic variables under study and finally a Monte Carlo Simulation analysis was carried out, which yields the maximum and minimum values that the environmental damage index can take in the coming years if the conditions in the analysis period remain constant. The correlation analysis presented positive and negative values; which is an indicator that in Ecuador there are provinces in which the relationship between economic growth and the environment is direct; while in others said correlation is inverse. Finally, with the Monte Carlo simulation, it is concluded that if conditions prevail, the provinces of Guayas and Pichincha will be the provinces with the greatest environmental damage, influenced by their growth.